“A Party of Forgetful Metaphors”. On the Problem of pragmatics of the classical form in Russian architecture of the 20th and early 21st c - Bass, Vadim G. (Actual Problems of Theory and History of Art, 2012)
The paper deals with the classical tradition in Russian architecture of the 20th – early 21st century. The specifi c uses of Classical order are examined as well as the architects’ intentions. The paper starts from the pre-revolutionary period, then the focus shift s to Stalinist architecture and Soviet Postmodernism of the late 20th century. Finally, the contemporary Moscow order architecture, e.g. by Dmitry Barkhin, is examined, which is based on citing of concrete historical buildings.